2012
DOI: 10.4172/2157-7099.1000145
|View full text |Cite
|
Sign up to set email alerts
|

Structural Studies on the Radio-Protective Effect of Lycopene (Tomato Supplementation) Against Hepatic Cellular Injury Induced by Chronic Doses of Gamma Radiation

Abstract: Background and aim: Antioxidants are substances that may protect our bodies against the effects of freeradicals. Free radicals are molecules produced when our body breaks down food, or by environmental exposures like radiation. Free radicals can damage cells, our goal of this work is to study the damage resulted by chronic low doses of gamma radiation using natural antioxidant like Lycopene that found in tomato that are available to most of the people especially those that work in the field of radiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…As a result, lycopene would safeguard cellular membrane from lipid peroxidation induced by radiation, thus maintaining the structure of small intestine and inhibiting monoamines release (Saada et al., 2010). Fathy Waer & Shalaby (2012) report demonstrated lycopene effects with dosage of 5 mg/kg daily on adult and healthy male albino rats exposed to radiation of (1/2) Gy. It showed that Lycopene induces great improvement in the cellular organoids structure against cellular damaged induced by the gamma radiation.…”
Section: Biological Activities Of Natural Antioxidants Against Divers...mentioning
confidence: 99%
“…As a result, lycopene would safeguard cellular membrane from lipid peroxidation induced by radiation, thus maintaining the structure of small intestine and inhibiting monoamines release (Saada et al., 2010). Fathy Waer & Shalaby (2012) report demonstrated lycopene effects with dosage of 5 mg/kg daily on adult and healthy male albino rats exposed to radiation of (1/2) Gy. It showed that Lycopene induces great improvement in the cellular organoids structure against cellular damaged induced by the gamma radiation.…”
Section: Biological Activities Of Natural Antioxidants Against Divers...mentioning
confidence: 99%